Eternal bits [digital files preservation]. - Smith, M.
The MIT Libraries is addressing the problem of maintaining and sharing digital content over the long haul with a project called DSpace. For this digital repository, a simple, open-source software application was built that not only accepts digital materials and makes them available on the Web but also puts them into a data management regime that helps to preserve them for generations to come. Other organizations worldwide have begun similar efforts including Cornell University, and the University of Toronto, the University of Cambridge. DSpace has a growing group of committed programmers distributed across the globe who continually maintain and improve it.
Keywords: DSpace Project; Web; Data management; Digital files preservation; Digital materials; Digital repository; Open-software application